PENGARUH KARAKTERISTIK PRIBADI, PEKERJAAN TERHADAP KINERJA DENGAN MODERASI BUDAYA ORGANISASI ( STUDI PADA DINAS KEBUDAYAAN PARIWISATA PEMUDA DAN OLAHRAGA KABUPATEN PATI ) - 11.4202.0113, Trevita Puspita Hadi (Jurnal Mahasiswa Pasca Sarjana, 2013)
In organizingthe activities of government and development position and role of civil servantsis very important. This is due toan elementof civil servants who carry out the state apparatus of governance and developmentin order to achieve national objectives. The human elementis an importantelement, becausethe human active and dominant rolein anyorganization. Programs and objectivesin order to achievethe necessary organizational support employee performance. The purposeof this studywas to analyzethe influence of personal characteristic sand job characteristics on employee performance with organizational culture of moderation. This study establishesthe employee population Department of Tourism Culture Youth and Sports, amounting to 12 0people with taking the censu smethod. Validit yanalysis tools, relibilitas test, test the coefficient of determination, F-test, regression analysis, Ttest, testm oderation.Results showed personal characteristics (X1) has apositiv eeffecton performance(Y). Job characteristics(X2) has apositive effect on the performance ofjob performance (Y). Ofthe independent variables, namel ypersonal characteristics and job characteristic sthat have a dominant influenc eon the performanc echaracteristics ofthe jobisvariable (X2).Personal characteristics variable sresults moderation with organizational culture, organizational culture variable sca nnot moderate the effect of job characteristics variables showed variable organizational culture organizational culture moderate theeffect ofjob characteristics on the performance variable. Keywords: personal characteristics, employment characteristics, employee performance, and organizational culture.